1981
DOI: 10.1172/jci110197
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Spermine as an Inhibitor of Erythropoiesis in Patients with Chronic Renal Failure

Abstract: A B S T R A C T Fetal mouse liver and normal human bone marrow cell cultures were used for studies on the inhibition of erythroid colony formation (CFU-E) by sera from anemic patients with end-stage renal failure and the polyamine spermine. Sera from each of eight predialysis uremic anemic patients with end-stage renal failure produced a significant (P < 0.001) inhibition of erythroid colony formation in the fetal mouse liver cell cultures when compared to sera from normal human volunteers. In vivo or in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
45
0
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(50 citation statements)
references
References 19 publications
4
45
0
1
Order By: Relevance
“…In addition, oxidative stress contributes to macrophage and vascular smooth muscle cell (VSMC) apoptosis, plaque instability, rupture, and thrombosis (1,6,7). Spermine, a polyamine product, is a reputed uremic toxin that has been implicated as a potential mediator of a number of the CKD-associated clinical abnormalities (22). Spermine administration has been shown to increase intracellular reactive oxygen species (ROS) in primary human cells and malignant tumor cell lines and induces apoptosis by activating the mitochondria-dependent intrinsic pathway signaling (23).…”
mentioning
confidence: 99%
“…In addition, oxidative stress contributes to macrophage and vascular smooth muscle cell (VSMC) apoptosis, plaque instability, rupture, and thrombosis (1,6,7). Spermine, a polyamine product, is a reputed uremic toxin that has been implicated as a potential mediator of a number of the CKD-associated clinical abnormalities (22). Spermine administration has been shown to increase intracellular reactive oxygen species (ROS) in primary human cells and malignant tumor cell lines and induces apoptosis by activating the mitochondria-dependent intrinsic pathway signaling (23).…”
mentioning
confidence: 99%
“…However, this level does not reach the range known as giving toxic effects on hematopoiesis (Mladenovic 1988). His serum spermine and spermidine, which are regarded as one kind of the hemopoietic-inhibitory factors (Radtke et al 1981), were within the normal range. This case also has not had chronic inflammatory state or osteitis fibrosa.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, many investigators believe that suppression of the bone marrow by uremic toxins also plays a significant role (Radtke et al 1981 (Delwiche et al 1986;Segal et al 1988). Their reasoning is that the specificity of potential erythropoietic inhibitor can not be ascertained (Delwiche et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…This state is regarded to be due to inhibitory effects of uremic sera on heme synthesis and erythroid progenitor cell (CFU-E) but not to their own marrow function. In addition to inadequate ESF production, inhibitors of erythropoiesis have been postulated to be responsible for the development of progressive anemia in uremic patients (Ohno et al 1978 ;Wallner et al 1978 ;Radtke et al 1981). The inhibitors which have been implicated include the polyamines such as spermine and spermidine (Radtke et al 1981) and parathromone (Meytes et al 1981) ; on the contrary, Caro and Erslev (1985) reported that the polyamine spermine is not specific for erythropoiesis and McGonigle et al, demonstrated that parathyoid hormone levels failed to correlate with anemia or inhibition of erythropoiesis in uremic patients (1984c).…”
mentioning
confidence: 99%
“…In addition to inadequate ESF production, inhibitors of erythropoiesis have been postulated to be responsible for the development of progressive anemia in uremic patients (Ohno et al 1978 ;Wallner et al 1978 ;Radtke et al 1981). The inhibitors which have been implicated include the polyamines such as spermine and spermidine (Radtke et al 1981) and parathromone (Meytes et al 1981) ; on the contrary, Caro and Erslev (1985) reported that the polyamine spermine is not specific for erythropoiesis and McGonigle et al, demonstrated that parathyoid hormone levels failed to correlate with anemia or inhibition of erythropoiesis in uremic patients (1984c). Target tissues such as animal bone marrow and fetal mouse liver have been used to detect inhibition of erythropoiesis by uremic serum, although these might not reflect all of the in vivo responses of uremic serum on erythropoiesis in the marrow.…”
mentioning
confidence: 99%